Critique, clinic, and care in times of COVID. Issue 2 (2nd September 2022) - Ingala, Emma
ABSTRACT: Critique has been recently accused of not being able to respond to the challenges of our times, such as the climate emergency and the pandemic crisis. The new materialisms, which have posited themselves as a corrective to critique's alleged overinflation of culture and language by proposing a (re)turn to matter, affirm that ours is a post-critical era. Against this diagnosis, the aim of this paper is to defend both the importance of critique for our current conjuncture and the need to rethink what it involves. Drawing from the work of Foucault, Deleuze, and Butler, I develop a specific but multidimensional understanding of critique that combats the vagueness and inconsistencies surrounding many post-critical approaches to this notion. Specifically, I suggest that critique entails (1) an enquiry into the conditions that structure, organise, and determine what can and cannot be perceived, experienced, and thought; (2) a clinical diagnosis or symptomatology of our present; (3) a political exercise of freedom; and (4) a practice of care. I conclude by showing how this conception of critique helps us to understand different dimensions of the Covid pandemic that might otherwise be ignored.